Conocimientos sobre tuberculosis y riesgo de abandono del tratamiento en pacientes con tuberculosis pulmonar-Red Pacasmayo - Aguilar Urcia, Laura Magaly (2019)
The present quantitative, descriptive-Correlational, cross-sectional research was conducted of May to June 2018 in the programs of the National Health Strategy for Prevention and Control of Tuberculosis of the RED-PACASMAYO, with the purpose of determine the relationship between the level of knowledge about tuberculosis and the risk of abandoning treatment. The sample universe consisted of 27 patients with pulmonary tuberculosis in treatment. Three instruments were applied: level of knowledge and risk of abandonment of treatment. The results are presented in tables of one and double entry, with numerical and percentage frequencies, where 63.0 percent of these presented an average level of knowledge, 29.6 percent their level of knowledge is high, and 7.4 percent his knowledge is low. On the other hand, 66.7 percent showed a low risk of abandonment of treatment, and 33.3 percent high. Regarding the double entry table, 55.6% have a medium level of knowledge and also have a low risk of abandonment, and 25.9% of patients have a high level of knowledge and their risk is high, 7.4% of patients Knowledge level is low and your risk is low. There is a highly significant statistical relationship (P = 0.001)